PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS ANIMASI PADA MATERI ARITMATIKA SOSIAL SISWA SMP - Mucti , Alfian (Jurnal Penalaran dan Riset Matematika, 2025)
This study aims to develop instructional media in the form of animated videos for the topic of Social Arithmetic in seventh-grade students at SMPN 4 Tarakan. The research was motivated by students’ low engagement and understanding in online learning during the pandemic, particularly regarding abstract contexts in Social Arithmetic. The method used is Research and Development (R&D), adopting the simplified Borg & Gall model up to the operational product revision stage. The video product was developed using Plotagon and Edpuzzle software and validated by experts in content, media, and instructional design. Validation results showed high feasibility percentages: 77.94% (content), 89.28% (media), and 92.50% (instructional design). Field testing on students also indicated the video was highly feasible, both in preliminary testing (90.97%) and operational field testing (89.97%). This study concludes that the developed animated video is highly appropriate as an alternative learning medium to improve the quality of mathematics instruction.